Cultural heritage and risk assessments: Gaps, challenges, and future research directions for the inclusion of heritage within climate change adaptation and disaster management. Issue 3 (24th June 2022) - Crowley, Kate; Jackson, Rowan; O'Connell, Siona; Karunarthna, Dulma; Anantasari, Esti; Retnowati, Arry; Niemand, Dominique
Abstract: Cultural heritage shapes our identity, delivers capacities, and exposes vulnerabilities, yet cultural heritage value and vulnerability are largely missing from conventional risk assessments. Risk assessments are a fundamental first step in identifying effective mechanisms for Climate Change Adaptation (CCA) and disaster management. However, by ignoring the influence of heritage, decision makers are limiting their understanding of risk and therefore opportunities vital for building and maintaining local resilience. We present findings from a synthesis of peer‐reviewed literature from the last 15 years on cultural heritage risk assessment for primarily CCA but with wider implications for disaster management. We identify a significant lack of research examining intangible aspects of heritage and their influence on risk and resilience. Across the literature, risk assessments focus largely on exposure in isolation from vulnerability or adaptive capacity and where vulnerability is included there is no consistent definition or criterion. We highlight that the most frequently used methods have minimal engagement with local community values, experience, and knowledge relating to heritage practice and customs. Community engagement is most often associated with 'professional experts' rather than members of a local community. Furthermore, the Global South is severely under‐represented with a research bias towards Europe and North America. We recommend an agile approach to future assessments with the adjustment of risk tool research and development to include participatory approaches. Future climate risk frameworks must incorporate community‐scale values to understand the role of cultural heritage in relation to adaptive capacity, vulnerability, and resilience.